1994
DOI: 10.1017/s0022215100127598
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound in the management of peritonsillar abscess

Abstract: A distinction between a peritonsillar abscess and peritonsillitis is useful clinically, as the former requires surgical drainage while the latter merely requires treatment with antibiotics. To evaluate the diagnostic implications of performing ultrasonography of the tonsils in patients with clinically diagnosed peritonsillar abscess, 27 patients underwent ultrasound examination before needle aspiration of the abscess was performed. Ultrasound was able to detect peritonsillar abscess in91 per cent of the cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 11 publications
1
16
2
2
Order By: Relevance
“…The sensitivity of transcutaneous US (80%) was lower compared to intraoral US (92.5%) in the same patients, however it was more specific (92.8%) compared to intra-oral US (90%). Ahmed et al 9 , in a study of 27 patients, reported a 90% sensitivity for transcutaneous US, better than our results, however inferior to the rate obtained with intra-oral US. Transcutaneous US had 5 false negative results, limiting its use to the diagnosis of peritonsillar abscesses.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The sensitivity of transcutaneous US (80%) was lower compared to intraoral US (92.5%) in the same patients, however it was more specific (92.8%) compared to intra-oral US (90%). Ahmed et al 9 , in a study of 27 patients, reported a 90% sensitivity for transcutaneous US, better than our results, however inferior to the rate obtained with intra-oral US. Transcutaneous US had 5 false negative results, limiting its use to the diagnosis of peritonsillar abscesses.…”
Section: Discussioncontrasting
confidence: 85%
“…al. 9 have suggested that needle aspiration is an accurate procedure for this diagnosis, in contrast to Scott et al 7 , that reached 89% sensitivity compared with computerized tomography. Computerized tomography is effective to diagnose deep neck affections, however, it is expensive, subject to complications due to use of contrast and difficult to access in emergency units 1,3 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Ultrasound (US) has been shown to reliably distinguish PTA from PTC in a number of small‐scale studies with adult patients . There is currently no literature addressing the use of US for peritonsillar infection in an exclusively pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…External (from the neck) ultrasound as a diagnostic procedure has been investigated in a series of 27 patients, where needle aspiration by an investigator blinded to the ultrasound result was taken as the gold standard . Trans‐cutaneous ultrasound had a sensitivity of 91% and a specificity of 80%.…”
mentioning
confidence: 99%